Disparities in bone density across contemporary Amazonian forager‐horticulturalists: Cross‐population comparison of the Tsimane and Shuar. Issue 1 (29th October 2019) - Madimenos, Felicia C.; Liebert, Melissa A.; Cepon‐Robins, Tara J.; Urlacher, Samuel S.; Josh Snodgrass, J.; Sugiyama, Lawrence S.; Stieglitz, Jonathan
Abstract: Objectives: This study investigates bone density across the life course among Bolivian Tsimane and Ecuadorian Shuar of Amazonia. Both groups are rural, high‐fertility forager‐horticulturalists, with high lifetime physical activity levels. We test whether Tsimane and Shuar bone density patterns are different from each other, and if both groups are characterized by lower osteoporosis risk compared to U.S. references. Methods: Anthropometric and calcaneal bone density data, obtained via quantitative ultrasonometry (QUS), were collected from 678 Tsimane and 235 Shuar (13–92 years old). Population and sex differences in QUS values (estimated bone mineral density, speed of sound, broadband ultrasound attenuation) by age group were assessed using Mann–Whitney U tests. Age‐related change and age at peak QUS value were determined using polynomial regressions. One‐way analyses of covariance assessed population‐level differences in QUS values by age group adjusting for body mass index. Participants aged 50+ years at elevated osteoporosis risk were identified using a T score < −1.8; binomial tests assessed risk compared to U.S. references. Results: Shuar males and females <50 years old have QUS values 3–36% higher than Tsimane, with differences evident in adolescence. Among Tsimane and Shuar, 49 and 23% of participants aged 50+ years old, respectively, are at high risk for osteoporosis, compared to 34% of Americans; Shuar osteoporosis risk is comparable to Americans, while Tsimane risk is elevated. Conclusions: Disparate patterns in QUS values are documented for Tsimane and Shuar, with pronounced differences early in life. Potential explanations for differences include gene–environment interactions and/or degree of market integration, which influences diet, activity profiles, pathogen exposures, and other lifestyle covariates. As Tsimane osteoporosis risk is greater than in the United States, findings point to alternative risk factors for low bone density that are not readily discernible in industrialized populations.